2006
DOI: 10.3168/jds.s0022-0302(06)72232-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in the Kinetics of Glucose and Urea in Holstein Calves

Abstract: Because weaning is the point when the nutrient composition of feed changes for the neonatal ruminant, the present experiment was conducted to assess the developmental changes in the kinetics of glucose and urea over this period, using stable isotopes of glucose and urea, at 4, 13, and 24 wk in calves. Plasma concentrations of nonesterified fatty acids, amino-N, urea-N, and insulin-like growth factor-I increased, but that of growth hormone decreased with age. The plasma glucose concentration increased at 13 wk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
2
18
1
3
Order By: Relevance
“…Nitsan et al (1971) reported similar values of plasma urea to animals fed whole milk and that receiving milk replacer containing soybean. Hayashi et al (2006) obtained plasma urea concentration values in the fourth week after calves' birth of approximately 24 mg dL −1 , which coincides partly with the values obtained in the current study for treating LV/HP and HV/HP. Because this parameter is strongly influenced by the diet consumed, the behavior of the curve HV/LP treatment could be explained by the milk replacer lower protein content.…”
Section: ------------------------------------------------------------supporting
confidence: 74%
“…Nitsan et al (1971) reported similar values of plasma urea to animals fed whole milk and that receiving milk replacer containing soybean. Hayashi et al (2006) obtained plasma urea concentration values in the fourth week after calves' birth of approximately 24 mg dL −1 , which coincides partly with the values obtained in the current study for treating LV/HP and HV/HP. Because this parameter is strongly influenced by the diet consumed, the behavior of the curve HV/LP treatment could be explained by the milk replacer lower protein content.…”
Section: ------------------------------------------------------------supporting
confidence: 74%
“…RT-PCR for the expression of Sglt-1 mRNA was performed by random hexamer primers. The RT-PCR quantification was made with the Light Cycler System (Roche Molecular Biochemicals; Hayashi et al 2006). Glyceraldehyde-3-phosphate dehydrogenase was included in the assays as a housekeeping gene.…”
Section: Sample Collection and Analysesmentioning
confidence: 99%
“…The weaning stress along with lower feed intake could be the reason for lower plasma glucose in both groups at this time period. Around weaning, the rates of irreversible loss and recycling of glucose decreased suggesting that glucose is preferably used as the energy source in suckling calves (Hayashi et al, 2006). Higher glucose levels in subsequent periods would suggest that calves in both groups were well adapted to the feeding regime and could have a better ability to utilize glucose.…”
Section: Discussionmentioning
confidence: 99%